Systemic immune effects of anesthetics and their intracellular targets in tumors - Luan, Ting; Li, Yi; Sun, Lihui; Xu, Siqi; Wang, Haifeng; Wang, Jiansong; Li, Chong (Frontiers in Medicine, 2022)
According to the result released by WHO (World Health Organization), non-communicable diseases have occupied four of the top ten current causes of death in the world. Cancer is one of the significant factors to trigger complications and deaths, and more than 80% patients with cancers need to receive anesthetics treatment. And during the operation, the neuroendocrine system will be stimulated to release a large amount of immunosuppressive factors and lead to continuous cell immunosuppression. A growing body of research has revealed that medication and therapeutics in perioperative period will also contribute to both the increased number and ability of tumor cells in blood circulation. All the factors mentioned will promote tumor cells’ metastasis to the distal end and further affect the prognosis in patients. This article will focus on the effects of anesthetic drugs on immune function and cancer, and review their latest targets on the tumor cells, in order to provide a theoretical basis for optimizing the selection of anesthetic drugs, exploring therapeutic targets and improving the prognosis of cancer patients.